Pendampingan Legalitas UMKM Desa Besowo, Kecamatan Kepung, Kabupaten Kediri - Hajril, M.; Nusantara, M.Billah Jaya; Rauf, Abdur; Nurlia, Siti; Abdullah, Khairunnisa; Sidiq, Muhammad Said (Fakultas Tarbiyah IAIN Kediri, 2023)
The presence of business legality is a fundamental aspect in any enterprise. Business legality serves as a standard that all business practitioners, including those operating small-scale businesses like MSMEs, must meet to have their businesses legally recognized. However, legal aspects of businesses are often overlooked by many business operators, including those in the MSME sector. This serves as the background for the development of the